Effect of fillers on key characteristics of sludge thermophilic anaerobic digestion. (October 2015) - Shao, Liming; Xu, Yuanshun; Wang, Tianfeng; Lü, Fan; He, Pinjing
Graphical abstract: Highlights: Filler-system improved digestion efficiency and digestate dewaterability. Fillers ameliorated the constitution of the microbial population. Effect of HRT on filler-system was explored. Abstract: In anaerobic digestion (AD) of sludge, AD efficiency and digested sludge (DS) dewaterability are critical factors. In this study, polyester non-woven fabric fillers were integrated into a sludge digester. The effect of such fillers on digestion was investigated in thermophilic temperature range in semi-continuous mode. Methane production of filler system and control reactor were significantly different ( P < 0.05, paired t -test). At hydraulic retention times of 18 days and 12 days, the corresponding methane yields from filler system were 140% and 161%, respectively, of the yields from control digester without filler. Improvement of DS dewaterability was uncertain during 110 days of operation. While after a longer period of digestion, filler system resulted in a lower normalized capillary suction time of DS (76.5 ± 21.6 s L/g total suspended solids) than control reactor (118.7 ± 32.9 s L/g total suspended solids). The results showed that the filler could improve thermophilic AD performance, except at too short hydraulic retention times.